New insights into the treatment of meningoencephalomyelitis of unknown origin since 2009: A review of 671 cases - Jeffery, Nick; Granger, Nicolas (Frontiers in Veterinary Science, 2023)
‘Meningoencephalomyelitis of unknown origin’ (MUO) - a collective term for a group of clinically-indistinguishable (but pathologically distinct) autoimmune diseases of the CNS – has become increasingly commonly recognized throughout the world. In the 1960s-1980s the focus was primarily on the pathological description of these conditions and, largely anecdotally, their response to glucocorticoids. The subsequent availability of magnetic resonance imaging for companion animals led to a focus on imaging characteristics and response of MUO to various immunosuppressive medications. Previous reviews have not found clear evidence of superiority of any specific treatment regimen. Here, we review outcomes in a further 671 dogs treated with various combinations of glucocorticoids and immunosuppressive drugs and reported since 2009, aiming to determine whether recommendations can be drawn from the material published during more recent decades. We observe that: (i) there is more complete information on outcome of MUO-affected dogs solely receiving glucocorticoids and these reports provide evidence to undermine the dogma that MUO inevitably requires treatment with glucocorticoids plus an immunosuppressive drug; (ii) there is far more information on the pharmacokinetics of cytarabine delivered by a variety of routes, revealing that previous dosing and duration of administration in dogs with MUO may not have been optimal; and, (iii) there is a large number of cases that could be available for entry into multi-institutional randomized controlled trials. Finally, we suggest new research avenues that might aid future clinical trials in MUO through improved understanding of etiological triggers and individual patterns of immune response, such as the impact of the gut microbiome, the potential of CSF flow cytometry, and the establishment of robust clinical scores for evaluation of treatment success.